Long-term outcomes and quality of life of high-risk neuroblastoma patients treated with a multimodal treatment including Anti-GD2 immunotherapy: a retrospective cohort study - Flaadt, Tim; Rehm, Jonas; Simon, Thorsten; Hero, Barbara; Ladenstein, Ruth L.; Lode, Holger; Grabow, Desiree; Nolte, Sandra; Crazzolara, Roman; Greil, Johann; Ebinger, Martin; Abele, Michael; et al. (Cancers, 2025)
Background: The incorporation of anti-GD2 antibodies such as ch14.18/SP2/0 into the multimodal treatment of high-risk neuroblastoma (HR-NB) patients has improved their outcomes. As studies assessing the long-term outcomes, long-term sequelae, and health-related quality of life (HRQoL) of this treatment are limited, this retrospective analysis aimed to explore these. Patients and Methods: Between 1991 and 2002, 65 children received a multimodal treatment, including ch14.18/SP2/0, for primary HR-NB. All received chemotherapy according to the NB90/NB97 trial, 51 received high-dose chemotherapy, and all received ch14.18/SP2/0 treatment. We analyzed the long-term sequelae and HRQoL (EORTC QLQ-C30), and evaluated overall and event-free survival (OS/EFS). Results: Twenty-five survivors were evaluated for HRQoL and long-term effects. All reported long-term sequelae, including ototoxicity in 16/25 (64%), cardiac toxicity in 6/25 (24%), and endocrine toxicity in 19/25 (76%) patients. Chronic diarrhea was reported in 20% of female patients. Seven patients developed autoimmune diseases. HRQoL scores were better across multiple scales than those of the matched German general population. Twenty-five-year OS and EFS were 50.8% (95% confidence interval: 31-55) and 43% (30.1-55.3), with 33 (50.8%) long-term survivors. Thirty-two patients died: 28 (43.1%) because of progression/relapse and 4 (6.2%) because of secondary neoplasms. Conclusions: Multimodal treatment, including ch14.18/SP2/0, can achieve long-term survival in HR-NB patients, with a substantial proportion of survivors reporting better HRQoL compared to the general population. All patients reported long-term side effects mostly attributable to chemotherapy and radiotherapy. The relatively high prevalence of autoimmune diseases and persistent diarrhea warrants additional longitudinal research on individuals treated with anti-GD2 antibodies.
Gesehen am 03.09.2025